Commented list of rare and protected vascular plants of inland water bodies of Estonia - Mäemets, Helle (Nature Conservation Research: Заповедная наука, 2016)
This presented overview of rare and protected hydrophytes, emergent plants and hygrophytes of inland water bodies of Estonia includes 60 species. In the commented list are indicated their position in the state protection categories I–III (last version in 2014), and under the Red List of Estonia (last version in 2008); marked are Natura 2000 species of the European Union. Most typical habitats for these rare species are: I. soft-water oligotrophic and semidystrophic lakes; II. mesotrophic lakes with Najas (Caulinia) flexilis and Potamogeton rutilus; III. alkaline fens and wet meadows; IV. brackish or freshwater coastal lagoons; V. undamaged river stretches; VI. open shallow littoral of the largest lakes of Peipsi (Pskovsko-Chudskoe) and of Võrtsjärv. Main threats of these habitats are briefly concerned, as well as the problem of conservation value of hybrids, based on the example of Sparganium species.